1999
DOI: 10.1093/geronb/54b.1.p44
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Predictors of Mortality in Old Age

Abstract: Cox regression models examined associations between 17 indicators of psychological functioning (intellectual abilities, personality, subjective well-being, and social relations) and mortality. The sample (N = 516, age range 70-103 years) comprised participants in the Berlin Aging Study assessed between 1990 and 1993. By 1996, 50% had died. Eleven indicators were identified as mortality risk factors at the zero-order level and six when age was controlled. Low perceptual speed and dissatisfaction with aging were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
221
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(245 citation statements)
references
References 42 publications
21
221
0
3
Order By: Relevance
“…In this study, we explored whether the associations between the age-related changes in depressive symptoms, arthritis diagnosis, and mortality remained after controlling for education, and agerelated changes in living arrangement, marital status, cognitive functioning, and illness burden (Anstey, von Sanden, Sargent-Cox, & Luszcz, 2007;Maier & Smith, 1999;Pessin, Rosenfeld, & Breitbart, 2002;Rapp, Gerstorf, Helmchen, & Smith, 2008).…”
Section: Covariates: Cognitive Functioning and Illness Burdenmentioning
confidence: 99%
“…In this study, we explored whether the associations between the age-related changes in depressive symptoms, arthritis diagnosis, and mortality remained after controlling for education, and agerelated changes in living arrangement, marital status, cognitive functioning, and illness burden (Anstey, von Sanden, Sargent-Cox, & Luszcz, 2007;Maier & Smith, 1999;Pessin, Rosenfeld, & Breitbart, 2002;Rapp, Gerstorf, Helmchen, & Smith, 2008).…”
Section: Covariates: Cognitive Functioning and Illness Burdenmentioning
confidence: 99%
“…Despite a general self-enhancement bias in well-being (e.g., the stability-despite-loss paradox), perceptions and evaluations of the self show sufficient reliable diversity allowing subtle differences to be powerful enough to predict outcomes such as morbidity (Levy, 2003) and mortality (Danner, Snowdon, & Friesen, 2001;Maier & Smith, 1999).…”
Section: Conceptual Implicationsmentioning
confidence: 99%
“…At an everyday and pragmatic level, low cognitive functioning may act as a risk factor for decline in well-being because it sets constraints on an individual's capacity to manage the routines of everyday life and thereby contributes to reduced satisfaction with life (cf. Maier & Smith, 1999).…”
mentioning
confidence: 99%
“…Even when physical health conditions are controlled, perceived health has been found to predict a variety of outcomes, including quality of life, service utilization, morbidity, and mortality [1,[3][4][5][6][7]. Due to the greater likelihood of health deterioration, the significance of perceived health among older populations is pronounced [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that persons with equivalent levels of physical conditions have different ratings of perceived health [9,10]. The discordance between objective and subjective health measures implies that the process of health appraisals is complex and goes beyond a simple summing of medical conditions or level of disability [1,4,6]. Moreover, the literature suggests that perceived health has a role to play in the health equation that is independent of its roots in actual physical health [9,10].…”
Section: Introductionmentioning
confidence: 99%